2020
DOI: 10.13102/sociobiology.v67i2.4992
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of essential oils of species from the genus Lippia against Nasutitermes corniger (Motschulsky) (Isoptera: Termitidae)

Abstract: Lippia is one of the main genera in the family Verbenaceae, with 200 species described. Despite its richness in bioactive molecules, with several scientifically proven applications, there is little information on the insecticidal potential of its species. This study aimed to assess the insecticidal potential of essential oils from the species Lippia thymoides (Martius & Schauer); Lippia lasiocalycina (Schauer) and Lippia insignis (Moldenk) against Nasutitermes corniger (Motschulsky) (Isoptera-Termitidae). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…O interesse pelos óleos essenciais reside em diferentes áreas do conhecimento com as mais variadas aplicações na indústria química como bioinseticida (DE ALBUQUERQUE LIMA et al, 2021;LIMA et al, 2021;OLIVEIRA, SANTOS et al, 2020), antifúngicos (ORTEGA-CUADROS et al, 2020;ROSANI et al, 2019), em cosméticos (GIMENES et al, 2021;SAGBO;MBENG, 2019), alimentos (MORONI; AIS; O'LEARY, 2022; LASCURAIN-RANGEL et al, 2022;BAUTISTA-HERNÁNDEZ et al, 2021) e farmacêutica, devido às suas propriedades anti-hipertensivas, anti-inflamatórias, atividades analgésica e antipirética, antimalárica, antimicrobiana ( LUCCA et al, 2022), antioxidante (MOLLER et al, 2020;JOSHI et al, 2018) e inibidor da acetilcolinesterase (KOBENAN et al, 2022;LI et al, 2020;MONIZ et al, 2019;SAIDI et al, 2020).…”
Section: óLeos Essenciais Como Fonte De Metabólitos Secundáriosunclassified
“…O interesse pelos óleos essenciais reside em diferentes áreas do conhecimento com as mais variadas aplicações na indústria química como bioinseticida (DE ALBUQUERQUE LIMA et al, 2021;LIMA et al, 2021;OLIVEIRA, SANTOS et al, 2020), antifúngicos (ORTEGA-CUADROS et al, 2020;ROSANI et al, 2019), em cosméticos (GIMENES et al, 2021;SAGBO;MBENG, 2019), alimentos (MORONI; AIS; O'LEARY, 2022; LASCURAIN-RANGEL et al, 2022;BAUTISTA-HERNÁNDEZ et al, 2021) e farmacêutica, devido às suas propriedades anti-hipertensivas, anti-inflamatórias, atividades analgésica e antipirética, antimalárica, antimicrobiana ( LUCCA et al, 2022), antioxidante (MOLLER et al, 2020;JOSHI et al, 2018) e inibidor da acetilcolinesterase (KOBENAN et al, 2022;LI et al, 2020;MONIZ et al, 2019;SAIDI et al, 2020).…”
Section: óLeos Essenciais Como Fonte De Metabólitos Secundáriosunclassified
“…was evaluated for its antimicrobial activity against bacteria (Gram-negative, Grampositive) and fungus (C. albicans) (Table 1). The analysis of the EO chemical composition of this species was carried out by Santos et al (2020), who found as main components β-myrcene (31.17%), (E)-ocimenone (24.10%), p-cymene (7.17%) and (Z)-ocimenone (6.51%), differing from the results obtained by Almeida et al (2018), who identified piperitenone oxide (57.55%) and limonene (20.69%) as major compounds in the EO of L. lasiocalycina. Despite the great interest in research on the biological properties of natural compounds obtained from the genus Lippia, studies related to the species L. lasiocalycina are still scarce, which emphasizes the search for more in-depth studies related to the antimicrobial activity of this EO.…”
Section: Lippiamentioning
confidence: 99%
“…Many essential oils have antitermitic activities, including oils from Lippia spp. [27] , Artemisia absinthium [28] , Lippia sidoides [29] , Chamaecyparis formosensis [30] , Liquidambar orientalis, and Valeriana wallichii [31] . Hutchins [32] reported that Aleurites fordii wood and meal extracts had antitermitic toxicity.…”
Section: Introductionmentioning
confidence: 99%